Synthesis, crystal structure and optoelectronic properties of [(CH3)3S]SnBr3 - Koutsoubogeras, John; Tsoureas, Nikolaos; Tagiara, Nagia S.; Kaltzoglou, Andreas (Journal of Coordination Chemistry, 2025)
We report on the preparation, crystal structure and spectral properties of the novel trimethylsulfonium tin tribromide, [(CH3)3S]SnBr3. The compound was synthesized by the solid-state reaction of (CH3)3SBr and SnBr2 in evacuated pyrex tubes at 150 °C. Single-crystal X-ray diffraction (SCXRD) studies at −173.15 °C show that it forms a 0D network of isolated pyramids of [SnBr3]− and (CH3)3S+ units in an orthorhombic structure (space group P212121, No. 19, a = 9.4508(8) Å, b = 14.1691(12) Å, c = 15.4409(14) Å)). Powder X-ray diffraction (PXRD) and Le bail profile fit analysis reveals that [(CH3)3S]SnBr3 adopts at room temperature a different crystal structure with space group (Pmmm, No. 47). Moreover, the oxidation of the compound occurs gradually in ambient air, towards the formation of [(CH3)3S)]2SnBr6 (space group Pa-3, No. 205). Multi-temperature Raman spectroscopy reveals that a fully reversible structural phase transition occurs for [(CH3)3S]SnBr3 between −36 and −56 °C, as evidenced by the changes in the vibrational modes of the [SnBr3]− ions. A direct band gap of 3.38 eV at RT is determined via UV–vis diffuse reflectance spectroscopy. Photoluminescence spectroscopy at −196.15 °C and 25 °C shows a weak luminescence signal with an emission maximum at ca. 460 nm for both temperatures.
Keywords: luminescence; multi-temperature Raman spectroscopy; Organic-inorganic compounds; Sn(II) halides; trimethylsulfonium cation